Roseburia spp. Abundance Associates with Alcohol Consumption in Humans and Its Administration Ameliorates Alcoholic Fatty Liver in Mice - Seo, Boram; Jeon, Kyungchan; Moon, Sunghyun; Lee, Kiuk; Kim, Woon-Ki; Jeong, Hyein; Cha, Kwang Hyun; Lim, Mi Young; Kang, Wondae; Kweon, Mi-Na; Sung, Joohon; Kim, Won; et al. (CELL PRESS, 2020)
Although a link between the gut microbiota and alcohol-related liver diseases (ALDs) has previously been suggested, the causative effects of specific taxa and their functions have not been fully investigated to date. Here, we analyze the gut microbiota of 410 fecal samples from 212 Korean twins by using the Alcohol Use Disorders Identification Test (AUDIT) scales to adjust for host genetics. This analysis revealed a strong association between low AUDIT scores and the abundance of the butyrate-producing genus Roseburia. When Roseburia spp. are administered to ALD murine models, both hepatic steatosis and inflammation significantly improve regardless of bacterial viability. Specifically, the flagellin of R. intestinalis, possibly through Toll-like receptor 5 (TLR5) recognition, recovers gut barrier integrity through upregulation of the tight junction protein Occludin and helps to restore the gut microbiota through elevated expression of IL-22 and REG3 gamma. Our study demonstrates that Roseburia spp. improve the gut ecosystem and prevent leaky gut, leading to ameliorated ALDs.
Keywords: TOLL-LIKE RECEPTOR-4; INTESTINAL MICROBIOTA; DISEASE PATHOGENESIS; BARRIER DYSFUNCTION; ASIAN PATIENTS; PROTECTS MICE; SP NOV.; INJURY; INFLAMMATION; STEATOHEPATITIS